DELETION IN MOVIE SUBTITLING - Agus Darma Yoga Pratama (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2018)
Abstrak Deletion in movie subtitling is a common practice due to limited space and time for subtitles to appear at the bottom of the screen. The limits are in terms of time for the subtitles to appear and be read by viewers and the number of characters to be shown on screen. Therefore, deletion is a strategy used especially for summarizing meaning or information from long dialogues. This is interesting because deletion should be implemented without deleting meanings or important information contained within the dialogues. Deletion is also considered to be used because viewers don't want to read long texts, as they are more focused on the scenes. This research is conducted to study types of deletion applied in movie subtitling and the impacts on delivering meanings to viewers. This research focuses on two movies, i.e. an adult action movie titled 13 Hours: The Secret Soldiers of Benghazi (2016) and a children animated movie titled Ice Age 5: Collision Course, in which English is the source language and Indonesian is the target language. These two movies are selected to compare deletion applied on action movies for adults and movies for children. This research applies deletion theory by Karamitroglou (1997) that summarizes deletion types in movie subtitling, such as functional expressions that don't contain semantic aspects, cumulative adjectives, and responsive expressions. Those three types of deletion don't interfere with delivery of meaning to viewers because they are supported by other aspects, such as dialogues, images, and music. The results of this research show that some taboo expressions are found in the adult action movie, whereas exclamations are found more in the animated movie. This is in line with the types of the movies, so selection of utterances for the subtitles is made according to the viewers' age. Some of the expressions are translated, while some other are not. This is due to technical aspects related to the number of characters that can be shown for each line of the subtitles. The translated expressions are responsive ones, like oh, fuck that, whoa, watch out, come on, all right, and yeah as well as cumulative adjectives, like a fucking massive heavy force. The types of expressions that are not translated are responsive utterances like Ew in the animated movie Ice Age 5, expressions that indicate additional information like (MEN ARGUING), (GUNSHOT), (LAUGHS) in the action movie 13 Hours, and expressions for additional information like (SCREAMING) and (GRUNTING) in Ice Age 5. The translated and untranslated expressions are functional expressions that don't contain semantic meaning, like well in both movies. Keywords: translation, deletion, expressions, strategy.